"I Am Not a Francophone": Identity Choices and Discourses of Youth Associating With a Powerful Minority. Issue 2 (3rd March 2016) - Groff, Cynthia; Pilote, Annie; Vieux-Fort, Karine
ABSTRACT: Taking a broad interest in the linguistic, educational, and identity issues relevant to young people, this article examines the experiences and discourses of linguistic minority youth in the French-dominant context of Québec City. Our analysis is based on qualitative interviews conducted with 10 young people who speak a language other than French at home and who chose to study in English at the postsecondary level. Beyond exploring the local impact of language policies, we focus on the identity choices these youth make in positioning themselves and the discourses that they appropriate in describing their sociolinguistic context. Findings suggest that tensions between linguistic groups in Québec are perpetuated through discourses that distance one group from another, including discourses of closed-mindedness and superiority. What the students in our study appear to be doing is rejecting a minority identity by invoking national and international scales through their discourses, scales in which English is dominant.